2019
DOI: 10.1002/ep.13202
|View full text |Cite
|
Sign up to set email alerts
|

Optimal sizing of gas engine in combined cooling heat and power systems by a proposed evaluation function and genetic algorithm optimization methods based on 4E analysis

Abstract: Determining the optimum size of the prime mover of combined cooling heating and power (CCHP) systems due to significant impact on energetic, environmental and economic results of these systems is very vital and essential. In this study, based on energy, exergy, environmental, and economic (4E) analysis the optimum capacity of the gas engine (GE) for CCHP systems have been investigated. The evaluation study performed by using a proposed evaluation function (EF) and genetic algorithm (GA) optimization methods fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…As elucidated in Ref. [ 34 ], the primary limitations of energy examination pertain to the overall efficacy of energy as well as fuel energy usage.…”
Section: E Assessmentmentioning
confidence: 99%
“…As elucidated in Ref. [ 34 ], the primary limitations of energy examination pertain to the overall efficacy of energy as well as fuel energy usage.…”
Section: E Assessmentmentioning
confidence: 99%
“…It has also been observed that this method has very good answers for complex and nonlinear objective functions. [51].…”
Section: Optimization Processmentioning
confidence: 99%